Transoceanic Introduction of a Freshwater Gastropod of Major ONE HEALTH Importance in Nigeria - Funmilayo Faith Hinmikaiye; Vincent Chikwendu Ejere; Catharina Clewing; Marcellin Rwibutso; Christian Albrecht (Water, 2026)
Invasive gastropods pose significant risks to ecosystem stability and public health by acting as intermediate hosts for parasites like Fasciola spp. During malacological surveys across Nigeria (2024–2025), populations of a previously unknown lymnaeid snail were discovered in two distinct habitats. Using an integrative taxonomic approach combining morphological examination and COI DNA barcoding, the species was identified as the Neotropical liver fluke snail Galba cubensis. Phylogeographical analysis revealed that Nigerian specimens share a common haplotype widespread in the Americas, Europe, and Asia, indicating a major transcontinental range expansion. While xenomonitoring of four specimens showed no current trematode infections, G. cubensis is a primary intermediate host for Fasciola hepatica. The establishment of this highly adaptable species in West Africa raises urgent ONE HEALTH concerns, including potential parasitic overspill and competition with native snails like Radix natalensis. Freshwater gastropod invasions in Nigeria, cryptic invasions in Africa, and future developments are discussed. The findings of this study emphasize the necessity of dedicated malacological surveys and risk management to address the spread of globally invasive freshwater snails.